Molecular mechanisms underlying sex and treatment-dependent differences in an animal model of cue-exposure therapy for cocaine relapse prevention - Peterson, Lucy; Nguyen, Jonathan; Ghani, Naveed; Rodriguez-Echemendia, Pedro; Qiao, Hui; Guwn, Sun Young; Man, Heng-Ye; Kantak, Kathleen M. (Frontiers in Neuroscience, 2024)
Environmental enrichment combined with the glycine transporter-1 inhibitor Org24598 (EE+ORG) during cocaine-cue extinction (EXT) inhibited reacquisition of 1.0 mg/kg cocaine self-administration in male but not female rats in a previous investigation. In this investigation, we determined if this treatment benefit in males required EXT training and ascertained the molecular basis for the observed sex difference in treatment efficacy. Nine groups of male rats trained to self-administer 1.0 mg/kg cocaine or receiving yoked-saline underwent EXT or NoEXT with or without EE and/or ORG. Next, they underwent reacquisition of cocaine self-administration or were sacrificed for molecular analysis of 9 protein targets indicative of neuroplasticity in four brain regions. Two groups of female rats trained to self-administer 1.0 mg/kg cocaine also underwent EXT with or without EE + ORG and were sacrificed for molecular analysis, as above. EE + ORG facilitated the rate of EXT learning in both sexes, and importantly, the therapeutic benefit of EE + ORG for inhibiting cocaine relapse required EXT training. Males were more sensitive than females to neuroplasticity-inducing effects of EE + ORG, which prevented reductions in total GluA1 and PSD95 proteins selectively in basolateral amygdala of male rats trained to self-administer cocaine and receiving EXT. Females were deficient in expression of multiple protein targets, especially after EE + ORG. These included total GluA1 and PSD95 proteins in basolateral amygdala, and total TrkB protein in basolateral amygdala, dorsal hippocampus, and ventromedial prefrontal cortex. Together, these results support the clinical view that sex-specific pharmacological and behavioral treatment approaches may be needed during cue exposure therapy to inhibit cocaine relapse.